A Critical Analysis and Discussion of Clinical Research Ethics in the Russian Federation and Their Implications for Western Sponsored Trials - Leintz, Christopher (Bioethics, 2014)
Globalization, political upheavals, and Western economic struggles have caused a geographical reprioritization in the realm of drug development and human clinical research. Regulatory and cost hurdles as well as a saturation of research sites and subjects in Western countries have forced the pharmaceutical industry to place an unprecedented level of importance on emerging markets, injecting Western corporate initiatives into cultures historically and socially isolated from Western-centric value systems. One of the greatest recipients of this onslaught of Western business and research practices is the Russian Federation. Namely, market forces are dictating a focused research initiative in the traditional emerging markets, but this focus may be at the expense of individual and societal dignity.